ENVIRONMENTAL TAXATION IN BRAZIL: ANALYSIS OF THE ECOLOGICAL ICMS, GREEN IPTU, GREEN IPI, CIDE-FUELS AND THE NEW SELECTIVE TAX - de Giorge Cerqueira, Homero (Revista Gênero e Interdisciplinaridade, 2025)
This study analyzes tax law as an instrument of environmental protection in Brazil, in light of the new tax legislation, particularly Constitutional Amendment 132 of 2023. The research is based on the recognition that taxes, in addition to their revenue-raising function, have an extra-fiscal dimension, capable of influencing behavior and guiding public policies. The study examines the evolution of environmental taxation in the country, highlighting initiatives such as the Ecological ICMS, the Green IPTU, the Green IPI, and the CIDE-Fuels (CIDE-Combustíveis), as well as the creation of the Selective Tax, provided for in the tax reform, to levy on products harmful to the environment. The study demonstrates that environmental taxation is supported by the Federal Constitution but depends on clear technical regulations, effective oversight, and the linking of revenues to environmental policies. The analysis highlights tensions between revenue collection and extra-fiscality, as well as the risk of regressive effects on the most vulnerable social groups. It is argued that environmental taxation should be integrated with other protection mechanisms, such as licensing and ecological zoning, to achieve regulatory effectiveness. It is concluded that, although limited by political, distributive, and technical aspects, environmental taxation constitutes a legitimate and necessary instrument to reconcile economic development and environmental preservation, provided it is accompanied by compensatory policies and transparency in fiscal management.